The Role of Financial Intermediary and the Contribution of Islamic Banking in Financing Micro, Small and Medium Enterprises in North Maluku - Sofyan Abbas (Jurnal Manajemen Bisnis, 2022)
Some of the research questions are as follows: (a). Whether Islamic banking financing in North Maluku is able to encourage the growth of the Micro, Small and Medium Enterprises sector (b). How do the implications of Islamic banking financing on MSMEs in North Maluku on strengthening the community's economy (c). Whether the synergy of MSME financing between Islamic financial institutions in North Maluku through optimizing the linkage of Islamic banking programs and Islamic microfinance institutions is a solution to strengthen the regional economy. Thus, the purpose of this study is to explore the contribution of Islamic banking through its financing in encouraging the growth of the MSME sector in the North Maluku province; Analyzing the positive implaculations of financing that has been disbursed by Islamic banks to MSMEs in order to increase capacity and strengthen the economic structure of the community in the North Maluku region; Elaborating and describing synergy between institutions and the role and function of financing between Islamic financial institutions in North Maluku in strengthening the local economy through optimization of linkage schemes or patternsThis study uses a descriptive qualitative research approach. The results of the study stated that the lack of optimal linkage program cooperation between Sharia Commercial Banks (BUS) and Sharia Microfinance Institutions (MFIs) is one of the reasons for the need for cooperation between these economic institutions. The non-optimal linkage program implemented by Islamic banks in the North Maluku region is due to the fact that Islamic banking in North Maluku currently still has a number of weaknesses that must also be taken into account by the Islamic bank itself so as not to negatively affect the bank's income to be obtained. The real condition of the Islamic Commercial Banks (BUS) above is actually reasonable to be taken into account by Islamic banks in the North Maluku region, because in principle the linkage financing pattern of Islamic banking must also meet economic aspects and sharia aspects, especially to the Micro, Small and Medium Enterprises (MSMEs) sector.